Increased expression and altered subcellular distribution of cathepsin B in microglia induce cognitive impairment through oxidative stress and inflammatory response in mice. Issue 1 (21st December 2018) - Ni, Junjun; Wu, Zhou; Stoka, Veronika; Meng, Jie; Hayashi, Yoshinori; Peters, Christoph; Qing, Hong; Turk, Vito; Nakanishi, Hiroshi
Abstract: During normal aging, innate immunity progresses to a chronic state. However, how oxidative stress and chronic neuroinflammation arise during aging remains unclear. In this study, we found that genetic ablation of cathepsin B (CatB) in mice significantly reduced the generation of reactive oxygen species (ROS) and neuroinflammation and improved cognitive impairment during aging. In cultured microglia, pharmacological inhibition of CatB significantly reduced the generation of mitochondria‐derived ROS and proinflammatory mediators induced by L‐leucyl‐L‐leucine methyl ester (LLOMe), a lysosome‐destabilizing agent. In the CatB‐overexpressing microglia after treatment with LLOMe, which mimicked the aged microglia, CatB leaked in the cytosol is responsible for the degradation of the mitochondrial transcription factor A (TFAM), resulting in the increased generation of mitochondria‐derived ROS and proinflammatory mediators through impaired mtDNA biosynthesis. Furthermore, intralateral ventricle injection of LLOMe‐treated CatB‐overexpressing microglia induced cognitive impairment in middle‐aged mice. These results suggest that the increase and leakage of CatB in microglia during aging are responsible for the increased generation of mitochondria‐derived ROS and proinflammatory mediators, culminating in memory impairment.